Принципи організації взаємодії компонент смарт мереж - Праховник, А.В.; Денисюк, С.П.; Коцар, О.В. (Технічна електродинаміка, 2012)
The questions of organization of interaction components at an implementation and functioning stage «Smart Grid» are considered. The substantive provisions of compatibility of components are certain taking into account application of principle "plug and play". The features of determination of levels and types of compatibility are lighted up on condition of joint coordination of functioning of both separate components and components with an electric network.